A legal study on the protection and welfare of laboratory animals in Malaysia / Noor Syakirah Khalil, Durratul Ain Mohamed Rafee and Khairun Nisa' Abdol Karim - Khalil, Noor Syakirah; Mohamed Rafee, Durratul Ain; Abdol Karim, Khairun Nisa' (2013)
This research project is about our analysis on the Malaysian Animal Welfare Bill, concerning on the welfare of laboratory animals particularly. This research project was set to point out the weaknesses existed in our current law and its enforcement in coping with the cruelty towards the laboratory animals. Since there is no specific provision that provide for the protection on the welfare of laboratory animals the issue arises here is, will there be any punishment by law and other alternatives mean to deter the offenders of such crime. This shows that our current still weak and has flaws. Since we have pointed out the flaws in current Act, we tried to suggest few measures that had been practiced in advanced in countries such as Australia and United Kingdom to act as a comparison in improvising our existing law. Our research project aim to provide a little bit of awareness for Malaysian and the party involve specifically that even animals use for experiment do had the right to be treated with proper care and handling